O professor primário português como intelectual: ‘eu ensino, logo existo’ The elementary school Portuguese teacher: “I think therefore I am” - Boto, Carlota (Revista Linhas, 2007)
O presente trabalho apresenta-se como uma reflexão histórica acerca do cariz intelectual impresso no ofício do professor primário. Formador de mentes, de almas e de corações, o professor primário lida diretamente com a transmissão – e talvez com a produção – de valores, de saberes, de normas de conduta prescritas. O professor primário forma o indivíduo para a civilidade e para o civismo. Sendo assim, ele situar-se-á, no campo da estruturação do moderno modelo escolar, como o ator privilegiado de fabricação de visões de mundo, que se deverão traduzir como consensos para o homem comum. O texto aqui exposto aborda, portanto, algumas representações acerca do lugar social ocupado pelo professor primário português, basicamente no período que abrange a segunda metade do século XIX e o primeiro decênio do século XX (imediatamente anterior à Proclamação da República em Portugal). Procurou-se tecer algumas considerações de ordem teórica e conceitual acerca da própria acepção de intelectual e a documentação recolhida traz à tona impasses e ambigüidades quanto à figura social do profissional encarregado de oferecer à infância as normas do ler, do escrever, do contar e do bom comportamento. Conclui-se que o professor primário é, assim, o veículo de propagação intelectual dos valores civilizatórios do Ocidente. PALAVRAS-CHAVE: Professor primário. Intelectual. Educação. História Social. Portugal This study is a historical reflection on the intellectual role of the elementary school teacher. A shaper of hearts, minds and souls, the elementary school teacher deals directly with the transmission – and even with the production – of prescribed values, knowledge and norms of conduct. The elementary school teacher prepares the individual to be civil and civic. Thus, the teacher is an element in the structuring of the modern school model and has an important role in the manufacturing of world views that should be presented as a consensus to common people. The text presented here addresses some representations about the social place occupied by the elementary school Portuguese teacher in the period from the second half of the nineteenth century to the first decade of the twentieth century (immediately before the Proclamation of the Republic in Portugal ). It seeks to elaborate some theoretical and conceptual considerations about the very reception of the intellectual. The documentation gathered reveals impasses and ambiguities concerning the social role of the professional responsible for presenting children the norms of reading, writing counting and good behavior. The paper concludes that the elementary school teacher is thus a vehicle for the intellectual propagation of Western civilizing values. KEY WORDS: Elementary school teacher.Intellectual. Education. Social History.